Technologies for removing pharmaceuticals and personal care products (PPCPs) from aqueous solutions: Recent advances, performances, challenges and recommendations for improvements - Liu, Tianqi; Aniagor, Chukwunonso O; Ejimofor, Marcel I; Tang, Kuok Ho Daniel; Chin, Bridgid; Chan, Yi Herng; Yiin, Chung Loong; Cheah, Kin Wai; Chai, Yee Ho; Lock, Serene Sow Mun; Yap, Kok Liang; Wee, Melvin Xin Jie; et al. (2023)
In recent years, the removal of pharmaceutical and personal care products (PPCPs) from aqueous solutions has been gaining a lot of attention from researchers throughout the world. This is particularly due to the concern about their potential hazards and toxicities, as they are classified as emerging contaminants. Thus, there is an increasing need to investigate removal technologies for PPCPs at a deeper and more holistic level. This review aims to provide the latest developments in removal technologies for PPCPs. It first succinctly describes the types, characteristics, and hazards of PPCPs on the environment and human health. It then comprehensively covers a wide range of technologies for removing PPCPs from aqueous solutions, comprising the adsorption process (using carbon-based adsorbents, plant biomasses, clay and clay minerals, silica-based adsorbents, zeolite-based adsorbents, polymers, and hybrid adsorbents), advanced oxidation processes (AOPs) (photocatalysis, Fenton or photo-Fenton, ozonation, ultrasonication, electrochemical oxidation, persulfate oxidation), membrane separation processes (ultrafiltration, nanofiltration, reverse osmosis), biodegradation processes (bacteria, algae, and fungi), and hybrid treatment (adsorption-AOP, AOP-membrane, membrane-biodegradation, and others). According to the specific experimental conditions, the reported removal efficiencies for adsorption, AOPs, membrane processes, biodegradation processes and hybrid treatment were 40-100%, 40-100%, 40-100%, 80-100% and 5-100%, respectively. In general, the findings revealed that biodegradation processes are favourable from the viewpoint of environmental sustainability. This review paper also highlights the challenges in this field of research, particularly the need to perform a thorough investigation of the operating parameters of the different removal technologies and conduct more studies on real industrial or sanitary wastewater. This review offers recommendations for future works to further advance the technical performances to eventually realize the wider application of these technologies at the industrial scale.